Thrombelastography (TEG) and Thrombin Generation Assay (TGA) in Severe Hemophilia Following Factor Replacement Therapy - Sarker, Tania T.; Brophy, Donald; Chitlur, Meera B. (Blood, 2015)
Background: Monitoring therapy in hemophilia is a major challenge. Measurement of factor levels is time consuming and not available in time to make clinical decisions. With the introduction of extended half-life factor products, determination of treatment frequency becomes important. Global hemostatic assays such as Thrombelastography (TEG) and Thrombin Generation Assay (TGA) may improve monitoring. Focused toward individualizing therapy, these assays may help determine treatment frequency based not just on Factor VIII PK (pharmacokinetic), but also on total hemostatic potential. Objective: To determine the correlation between TGA and TEG parameters, and Factor activity and half-life (t1/2). Design/Methods: With IRB approval and participant consent baseline FVIII activity was obtained at enrollment, 15minutes, 1, 4, 8, 24 and 48 hours post factor replacement in patients who had not received replacement factor for a minimum of 72 hours and were not bleeding. FVIII:C, TEG, and TGA at each time point were measured. Non-compartmental PK analysis was performed on each individual patient profile to measure Factor VIII terminal half-life (t 1/2), mean normalized factor clearance rate and volume of distribution at steady-state (Vdss). Pearson correlation statistical analyses on other variables were performed using JMP ¨ Pro version 12.0.1 (SAS Institute, Cary, NC, USA) Results: 27 patients with hemophilia have enrolled, with a median age of 14 years (range: 2-24 years). 9 patients were eliminated from analysis because of a diagnosis of inhibitors (n=1), factor activity >1% (n=4), inadequate sample collection (n=2), patient on episodic factor replacement (n=1), and inaccurate TGA time point (n=1). The mean Factor level prior to factor administration, after elimination of the subjects (n=18) was 0.4%. As expected, our results indicate a rise in ETP and Factor activity following factor replacement, peaking at 15 minutes post infusion. The mean normalized factor clearance rate was 3.3 ± 1.2ml/h/kg. The Vdss was 2.3 ± 1 L and Factor VIII t½ was 11.5 ± 3 hours. There were strong correlations between ETP and FVIII:C (R2=0.65; p<0.0001), Peak and FVIII:C (R2=0.6; p<0.0001), R Time and Factor VIII:C (R2=0.71; p<0.0001), Peak and R Time (R2=0.59; p<0.0001), ETP and R Time (R2=0.51; p<0.0001) as shown in table 1. Table 1Correlation data on Factor VIII:C with TGA & TEG Parameters; and TGA parameters with TEG R timeR2P-valueTGA Parameters (Peak & ETP)ETP and Factor VIII:C0.65p<0.0001Peak and Factor VIII:C0.60p<0.0001TEG Parameter (R Time)R Time and Factor VIII:C0.71p<0.0001TEG and TGA ParametersPeak and R Time0.59p<0.0001ETP and R Time0.51p<0.0001 Conclusions: Global hemostatic assays are less expensive than traditional PK testing and are available at the time of care decisions. Results of global coagulation assays (TEG and TGA) correlated closely with FVIII activities. Global assays may predict breakthrough bleeding independent of factor levels, representing an improvement in monitoring over traditional PK. With the emergence of the bioengineered extended half-life factor products, there is a renewed interest in pharmacokinetic analysis and individualization of therapy. Assays like TEG provide the opportunity to receive feed back in real time that corresponds to FVIII activity, and enable us to make treatment decisions rapidly for each individual patient. Since these assays measure more than just the factor activity, the parameters such as ETP on TGA may be more prognostic of bleeding tendency, as has been shown previously. Pharmacokinetic and pharmacodynamics analysis of this data is ongoing. Our small sample size precludes us from making global predictions. Larger multi center trials would assist in confirming these findings. No relevant conflicts of interest to declare.